Marketing Strategy of Arumanis Mango Fruit UD Sumber Bumi in Alaskandang Village Probolinggo Regency - Hidayat, Satrio Adnan; Yektiningsih, Endang; Suhardjono, Hadi (Politeknik Negeri Jember, 2025)
The research location was taken at UD Sumber Bumi Probolinggo. This study aims to identify and analyze what are the strengths, weaknesses, opportunities, and threats and provide recommendations for alternative strategies and priority strategies in marketing arumanis mango at UD Sumber Bumi in Alaskandang Village, Probolinggo Regency. This research takes samples, namely Business Owners and Experts who are experts in their fields. The data used are primary and secondary data. The data analysis techniques used are SWOT analysis and QSPM analysis. The results of the research conducted show that: The priority of the marketing strategy for arumanis mango produced by UD Sumber Bumi is to intensively promote in various media in order to be able to fight competitors despite unstable economic conditions with a TAS score of 4.23.